2019
DOI: 10.1139/cjce-2017-0266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of light-frame wood buildings

Abstract: This research project deals with dynamic field testing of light-frame wood buildings with wood based shear walls. The primary objective of the investigation is to evaluate the code formula for estimating light wood frame building's fundamental period, through intensive field testing and numerical modelling. The project also aims to propose an alternative simplified rational approach where applicable. The thesis provides insight to the ambient vibration testing procedures of light-frame wood buildings and expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Additionally, it matches well with similarly shaped and sized wooden structures observed in the study of Hafeez et al, 2019 [35]. This suggests that in addition to repeated measurements, future observation-based values in regular and irregular structures could also be validated against existing measurements in published compilations, like the instrumented buildings in the CESMD (Center for Engineering Strong Motion Data) database, and targeted campaigns, such as described by Hafeez et al [35] in their study of 41 wood-framed structures in Canada.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, it matches well with similarly shaped and sized wooden structures observed in the study of Hafeez et al, 2019 [35]. This suggests that in addition to repeated measurements, future observation-based values in regular and irregular structures could also be validated against existing measurements in published compilations, like the instrumented buildings in the CESMD (Center for Engineering Strong Motion Data) database, and targeted campaigns, such as described by Hafeez et al [35] in their study of 41 wood-framed structures in Canada.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed high similarity between the dynamic properties of these two buildings [7]. Hafeez et al studied dynamic properties of 32 light wood frame buildings and concluded that it was inaccurate to take the height of structures as the sole variable in determining the fundamental period of timber structures [8]. Recently, more mass timber buildings in Canada [3][4][5] and Europe [9] have been tested under dynamic loads at the serviceability level.…”
Section: Introduction 567mentioning
confidence: 99%
“…The research results showed that the anisotropy of wood properties negatively affects the stress-strain state of structures, which emphasizes the need to take this factor into account in design calculations and scientific research. In addition, it was found that the use of reinforcing stiffeners is an effective design solution for increasing the local stability [22] of compressed plywood slab sheathing and also helps to reduce the material intensity of plywood slab sheathing [23].…”
Section: Introductionmentioning
confidence: 99%